New insights into the role of pH, metal ions, and insoluble solids in the coproduction of fumarate and malate by Rhizopus delemar - Brink, Hendrik Gideon (University of Pretoria, 2022)
Dissertation (MEng (Chemical Engineering))--University of Pretoria, 2022.